AN INTEGRATED APPROACH TO PROBLEMS AND SOLUTIONS OF THE ARAL SEA - Abdunazarov Lutfillo Mamanovich; Rakhmonaliev Behruzbek Dilmurodjon’s Ogli; Meliqo’ziyeva Maxliyo Saydali's Qizi (Western European Studies, 2023)
An integrated approach to a comprehensive analysis of the complex of problems affecting the Aral Bay region is presented, and comprehensive solutions for its restoration are proposed. The Aral Sea has experienced severe environmental degradation, socio-economic problems and negative health impacts due to changing water resources, climate change and unsustainable agricultural practices. Through an integrative lens, this study explores the interconnectedness of these issues and highlights the need for a coordinated response. The article explores broadbased strategies such as sustainable water management, community-based resilience, ecological restoration and international cooperation to address the multi-faceted challenges posed by the Aral Sea in an attempt to achieve a harmonious balance between the environment and human well-being. . , will be discussed.
Keywords: Aral Sea; integrated approach; environmental degradation